EFISIENSI BIAYA LOGISTIK DENGAN FASILITAS KEPABEANAN PUSAT LOGISTIK BERIKAT: IMPIAN ATAU KENYATAAN? - Nurkhamid, Muh; Rahayu, Soeprat Teguh (JURNAL PERSPEKTIF BEA DAN CUKAI, 2020)
ABSTRACT: Research with this qualitative method aims to prove the impact of providing the Customs Center for Bonded Logistics Centers (PLB) to the domestic industry in the form of logistics cost-efficient. Research instruments in the form of interviews with 13 PLB entrepreneurs who have the theme of support for different sectors, government agencies (DJBC), the Indonesian Logistics Association, practitioners in logistics, the Indonesian Textile Association, and the Association of Indonesian Bonded Logistics Centers. The study concludes that PLB has increased the efficiency of the logistics costs of the domestic industry in the form of a decrease in dwelling time for each PLB entrepreneur who is the object of research; accelerating the fulfillment of raw materials for local industries; Cost Recovery efficiency for the Mining Industry; time and cost efficiency of the licensing process in customs procedures; and efficiency of production costs for the domestic manufacturing industry with a just in the time inventory system. In general, PLB has also triggered an increase in the economy, especially in the Indonesian textile industry sector. For the PLB to run more optimally, the government must complete certainty of the aspects of taxation, certificate of origin, and the government's support for the sustainability of the downstream textile industry, which is feared to be out of business due to the policy of bringing in semi-finished raw materials through PLB.Keywords: Customs Facilities, Bonded Logistics Center, logistics costs, dwelling time, textile industry.    ABSTRAK: Penelitian dengan metode kualitatif ini bertujuan membuktikan dampak pemberian Fasilitas Kepabeanan Pusat Logistik Berikat (PLB) terhadap industri dalam negeri berupa efisiensi biaya logistik. Instrumen penelitian berupa wawancara terhadap 13 pengusaha PLB yang memiliki tema dukungan terhadap industri yang berbeda-beda, instansi pemerintah (DJBC), Asosiasi Logistik Indonesia, praktisi di bidang logistik, Asosiasi Pertekstilan Indonesia, dan Perhimpunan Pusat Logistik Berikat Indonesia. Penelitian menyimpulkan bahwa PLB telah meningkatkan efisiensi biaya logistik industri dalam negeri berupa: penurunan dwelling time pada masing-masing pengusaha PLB yang menjadi obyek penelitian; percepatan pemenuhan bahan baku bagi industri dalam negeri; efisiensi Cost Recovery untuk Industri Pertambangan; efisiensi waktu dan biaya atas proses perizinan pada prosedur kepabeanan; dan efisiensi biaya produksi bagi industri manufaktur dalam negeri dengan sistem just in time inventory. Secara umum, PLB juga telah memicu peningkatan perekonomian khususnya pada sektor industri tekstil Indonesia. Agar PLB berjalan semakin optimal maka pemerintah harus menyelesaikan kepastian aspek perpajakan, certificate of origin, serta keberpihakan pemerintah terhadap keberlangsungan industri tekstil sektor hilir yang dikhawatirkan akan gulung tikar akibat kebijakan mendatangkan bahan baku setengah jadi melalui PLB. Kata Kunci: Fasilitas Kepabeanan, Pusat Logistik Berikat, biaya logistik, dwelling time, industri tekstil.